Pravastatin chitosan nanogels-loaded erythrocytes as a new delivery strategy for targeting liver cancer - Gamaleldin I. Harisa; Mohamed M. Badran; Saeed A. AlQahtani; Fars K. Alanazi; Sabry M. Attia (Elsevier, 2016)
Chitosan nanogels (CNG) are developed as one of the most promising carriers for cancer targeting. However, these carriers are rapidly eliminated from circulation by reticuloendothelial system (RES), which limits their application. Therefore, erythrocytes (ER) loaded CNG as multifunctional carrier may overcome the massive elimination of nanocarriers by RES. In this study, erythrocytes loaded pravastatin-chitosan nanogels (PR-CNG-ER) were utilized as a novel drug carrier to target liver cancer. Thus, PR-CNG formula was developed in nanosize, with good entrapment efficiency, drug loading and sustained release over 48 h. Then, PR-CNG loaded into ER were prepared by hypotonic preswelling technique. The resulting PR-CNG-ER showed 36.85% of entrapment efficiency, 66.82% of cell recovery and release consistent to that of hemoglobin over 48 h. Moreover, PR-CNG-ER exhibited negative zeta potential, increasing of hemolysis percent, marked phosphatidylserine exposure and stomatocytes shape compared to control unloaded erythrocytes. PR-CNG-ER reduced cells viability of HepG2 cells line by 28% compared to unloaded erythrocytes (UER). These results concluded that PR-CNG-ER are promising drug carriers to target liver cancer. Keywords: Erythrocytes, Hypotonic preswelling, Chitosan nanogels, Pravastatin, Liver targeting